Exercise-Induced Adult Cardiomyocyte Proliferation in Mammals - Zhang, Guo-liang; Sun, Ming-li; Zhang, Xin-an (Frontiers in Physiology, 2021)
Loss of cardiomyocytes is a vital manifestation and predisposing factor of many cardiovascular diseases and will eventually lead to heart failure. On the other hand, adult mammalian cardiomyocytes have a very limited regenerative capacity and cannot achieve self-repair of the myocardium after injury. Therefore, it is necessary to promote regeneration and repair of the myocardium through effective intervention means. Exercise plays an important role in the prevention and rehabilitation of cardiovascular diseases. Exercise can improve ischemia-reperfusion injury, reduce the size of the infarcted area, and improve the quality of life of patients. In addition, exercise has also been shown to be able to elevate the proliferative potential of adult cardiomyocytes and promote myocardial regeneration. Studies have shown that newly formed cardiomyocytes in adult mammalian hearts are mainly derived from pre-existing cardiomyocytes. By regulating various cytokines, transcription factors, and miRNAs, exercise can promote the dedifferentiation and proliferation of pre-existing cardiomyocytes to form new cardiomyocytes. Therefore, this paper focuses on the recent research progress of exercise-induced adult cardiomyocyte proliferation and explores its potential molecular mechanism.